Metode Mabac Dalam Penentuan Kenaikan Gaji Karyawan - Winanda Aprilia (U-NET Jurnal Teknik Informatika, 2024)
PT.Growth Asia Medan is a company engaged in steel production. Employees are the main object in HR studies to make the company's development increase, the success of the company's development can not be separated from the process of capacity activities of employees (workers) who do their work in the company, and in the process of doing their work a worker must be assessed, and employee appraisal should use an accurate method. and a good way, and has clear benchmarks so that fair in terms of employee assessment will be created, PT. Growth Asia Medan so far has not been optimal where the process is related to HR assessment. The assessment of these aspects is still using the manual method, so the accuracy of the results is not maximized, so we need a system that can provide convenience in determining a decision-making related to employee assessment for salary increases. To solve this problem the author designed a decision support system using the Mabac method in determining employees who are entitled to a salary increase. One of the methods used for decision support systems is the Mabac method which is able to simplify an unstructured complex problem.